Can Clinicians Predict Which Patients Respond Best to a Specific Treatment? A Systematic Review of Low Back Pain Moderators in Primary Care - Tayla Douglas; Hazel Jenkins; Leticia Correa; Leandro Nogueira; Annika Young; Mark Hancock (Journal of Orthopaedic & Sports Physical Therapy, 2026)
OBJECTIVE: To synthesise and critically evaluate evidence on treatment effect moderators in the primary care management of low back pain (LBP). DESIGN: Systematic review of randomised controlled trials (RCTs) and secondary analyses of RCTs. LITERATURE SEARCH: Medline, EMBASE, CINAHL and Cochrane Library were searched from inception to August 2025. STUDY SELECTION CRITERIA: RCTs investigating moderators for primary care interventions in non-specific LBP. DATA SYNTHESIS: Data were synthesised by exploring data clusters (similar intervention-moderator combinations) and examining high-quality evidence with promising effects. The quality of moderation analyses was assessed using the Instrument for assessing the Credibility of Effect Moderation Analyses (ICEMAN) tool and trial quality was assessed using the Physiotherapy Evidence Database (PEDro) scale. Study diversity precluded meta-analysis. RESULTS: Seventy-three studies were identified. The studies were highly heterogeneous with almost no repeated investigations of the same intervention-moderator combination. While RCT quality was generally high, moderation analysis quality was poor. Six studies (8% of 73) prioritised effect moderation as the primary aim. The remaining studies tended to analyse available data post-hoc rather than assessing theory driven moderators. Ten higher-quality analyses did not identify any clearly important moderators. Results were inconclusive due to high uncertainty (e.g. wide confidence intervals, lack of statistical significance) and conflicting findings. Some promising moderators were identified in fair-quality analyses, for example, graded exposure appeared more effective for those with high catastrophising. CONCLUSION: We identified a broad, but superficial body of literature on effect moderation in LBP primary care. The promising moderators identified require further testing before they can be recommended for clinical practice.